Knockdown of hypocretin attenuates extended access of cocaine self-administration in rats. (November 2018) - Schmeichel, Brooke; Matzeu, Alessandra; Koebel, Pascale; Vendruscolo, Leandro; Sidhu, Harpreet; Shahryari, Roxana; Kieffer, Brigitte; Koob, George; Martin-Fardon, Rémi; Contet, Candice
Abstract The hypocretin/orexin (HCRT) neuropeptide system regulates feeding, arousal state, stress responses, and reward, especially under conditions of enhanced motivational relevance. In particular, HCRT neurotransmission facilitates drug-seeking behavior in circumstances that demand increased effort and/or motivation to take the drug. The present study used a shRNA-encoding adeno-associated viral vector to knockdownHcrt expression throughout the dorsal hypothalamus in adult rats and determine the role of HCRT in cocaine self-administration. ChronicHcrt silencing did not impact cocaine self-administration under short-access conditions, but robustly attenuated cocaine intake under extended access conditions, a model that mimics key features of compulsive cocaine taking. In addition, Hcrt silencing decreased motivation for both cocaine and a highly palatable food reward (i.e., sweetened condensed milk; SCM) under a progressive ratio schedule of reinforcement, but did not alter responding for SCM under a fixed ratio schedule. Importantly, Hcrt silencing did not affect food or water consumption, and had no consequence for general measures of arousal and stress reactivity. At the molecular level, chronicHcrt knockdown reduced the number of neurons expressing dynorphin (DYN), and to a smaller extent melanin-concentrating hormone (MCH), in the dorsal hypothalamus. These original findings support the hypothesis that HCRT neurotransmission promotes operant responding for both drug and non-drug rewards, preferentially under conditions requiring a high degree of motivation. Furthermore, the current study provides compelling evidence for the involvement of the HCRT system in cocaine self-administration also under low-effort conditions in rats allowed extended access, possibly via functional interactions with DYN and MCH signaling.